Changing Clinician Practices and Attitudes Regarding the Use of Antiretroviral Therapy for HIV Treatment and Prevention: Results from the HPTN 065 Study. (January 2017) - Buchacz, Kate; Farrior, Jennifer; Beauchamp, Geetha; McKinstry, Laura; Kurth, Ann E.; Zingman, Barry S.; Gordin, Fred M.; Donnell, Deborah; Mayer, Kenneth H.; El-Sadr, Wafaa M.; Branson, Bernard; ,
As part of the HPTN 065 study in the Bronx, New York and Washington, the authors, we surveyed clinicians to assess for shifts in their practices and attitudes around HIV treatment and prevention. Antiretroviral therapy (ART)-prescribing clinicians at 39 HIV care sites were offered an anonymous Web-based survey at baseline (2010-2011) and at follow-up (2013). The 165 respondents at baseline and 141 respondents at follow-up had similar characteristics—almost 60% were female, median age was 47 years, two-thirds were physicians, and nearly 80% were HIV specialists. The percentage who reported recommending ART irrespective of CD4 count was higher at follow-up (15% versus 68%), as was the percentage who would initiate ART earlier for patients having unprotected sex with partners of unknown HIV status (64% versus 82%), and for those in HIV-discordant partnerships (75% versus 87%). In line with changing HIV treatment guidelines during 2010 to 2013, clinicians increasingly supported early ART for treatment and prevention.